2022
DOI: 10.1002/wer.1680
|View full text |Cite
|
Sign up to set email alerts
|

The fate and removal of pharmaceuticals and personal care products within wastewater treatment facilities discharging to the Great Bay Estuary

Abstract: Pharmaceuticals and personal care products (PPCPs) are contaminants of emerging concern that derive primarily in the water environment from combined sewer overflows and discharges from industrial and municipal wastewater treatment facilities (WWTFs). Due to incomplete removal during wastewater treatment, PPCP impacts to aquatic ecosystems are a major concern. The Great Bay Estuary (New Hampshire, USA) is an important ecological, commercial, and recreational resource where upstream WWTFs have recently been unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Further, larger facilities often have more stringent discharge limits, which often require longer retention times in the treatment plant in comparison to the smaller facilities. Interestingly, studies have indicated that longer sludge retention time in biological treatment processes at the WRRF result in improved PPCP removal [17] [18].…”
Section: Discussionmentioning
confidence: 99%
“…Further, larger facilities often have more stringent discharge limits, which often require longer retention times in the treatment plant in comparison to the smaller facilities. Interestingly, studies have indicated that longer sludge retention time in biological treatment processes at the WRRF result in improved PPCP removal [17] [18].…”
Section: Discussionmentioning
confidence: 99%